Leveraging Quizizz as a Supportive Digital Approach in English Instruction for Students with Special Needs - Dita Nur Aini; Rinda Rinda (JETS, English Department of University of Uluwiyah Mojokerto, 2026)
Teaching English to students with special needs calls for instructional strategies that are both adaptive and sensitive to learners' emotional and cognitive circumstances. In special education settings, conventional teaching methods frequently restrict student engagement and comfort during the learning process. This research set out to examine how Quizizz functions as a supportive digital tool in English instruction for students with special needs. Using a qualitative descriptive design, the study took place at a special school and involved students with special needs together with their English teacher. Information was gathered through classroom observation, documentation, and the teacher's own reflections while Quizizz was being implemented in English lessons. The material collected was then examined qualitatively to uncover patterns concerning student engagement, comfort in learning, and the ways instruction was adapted. Results revealed that incorporating Quizizz fostered a learning environment that was both more supportive and more engaging. Students displayed greater enthusiasm and willingness to take part in lessons, and the platform's interactive elements appeared to ease their learning-related anxiety. Furthermore, Quizizz gave the teacher room to tailor instructional approaches to match each student's capabilities, reinforcing an inclusive, learner-centered style of teaching. Based on these results, Quizizz can be regarded as a worthwhile digital strategy for supporting English instruction among students with special needs.